"Seeds for a New Life": Modernity and the Pacific Turn in the Progressive Era. (July 2020) - Chen, Constance
Abstract: Since the colonial era, the ideological and cultural usefulness of Asia has changed with evolving American needs. This article argues that the Progressive Era turn toward the Pacific world marked a new epoch and mode of transnational interchange as a diverse array of Americans traveled to China and Japan. Encounters with Asianness in situ would lead to a reinvention of the U.S. worldview in the late nineteenth century. The question at hand for certain Americans was how to become "modern, " to germinate "seeds for a new life" that would ensure the prosperity and well-being of the United States amidst momentous global changes. Instead of being antimodernist, the fetishization of Asia served as a way to rein in and define modernity for American purposes. In the process, modernist Orientalism became a framework for imagining China and Japan and their cultural practices. Buddhism, in particular, was reconceptualized as a hybrid entity that seemed to be emblematic of the dawn of a new era. Ultimately, the flow of ideas and peoples between Asia and the United States enabled Americans to construct a global "modern" identity for themselves and to carve out a prominent role for the nation within the international community.